DIDACTIC POSSIBILITIES OF DIGITAL EDUCATIONAL PLATFORMS AND INTERACTIVE METHODS IN TEACHING FOREIGN LANGUAGES - Tursunova Ezoza Ravshanjonovna (TILSHUNOSLIK VA CHET TILLARNI O‘QITISHDA ZAMONAVIY RAQAMLI TEXNOLOGIYALARDAN FOYDALANISH MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article examines the significance of digital technologies and interactive methods in teaching foreign languages. Today, the role of digital technologies is extremely important in engaging young people in education and enhancing the learning process. In particular, modern interactive methods and digital platforms used in foreign language learning, such as mobile applications, online courses, virtual learning environments, and useful platforms, create new opportunities for both teachers and students. Additionally, digitized education tailored to foreign language learning contributes to the development of cultural exchange and global communication.